OPTIMASI TUTUPAN LAHAN RUANG TERBUKA HIJAU PUBLIK KOTA KOTAMOBAGU - Priawanto ., Kasim; Bobby ., Polii; Zetly ., Tamod (AGRI-SOSIOEKONOMI, 2017)
This study was conducted to (1) identify the public green opened space based on covering area in Kotamobagu city and (2) analyze the optimization of development for the public green opened space in Kotamobagu city. Method used in this study was the mix method. The mix method was applicated to study and analyze the index of covering area based on size of existing of the public green opened space. This existing public green opened space would define direction of continouos public green opened space development in Kotamobagu city. Result of the study showed that (1) the size of public green opened space in Kotamobagu city was 1.059 ha with the covering area index of 16 percents. The size of public green opened space in Kotamobagu city consists of several types of public green opened spaces, which were not optimally managed such as those at Pobundayan city parks, Gelora Ambang city parks and Bonawang city forest. (2) Development of public green opened space in Kotamobagu city was focused on minimum size target of 20 percents from entired size of Kotamobagu areas as the indicator of green city standard. The potential locations for size development were including the areas of plantation, city forest and river common border of 50 m.